Cas9-AAV6-engineered human mesenchymal stromal cells improved cutaneous wound healing in diabetic mice - Waracharee Srifa (Nature Portfolio, 2020)
Human mesenchymal stromal cells are a promising source for cell-based therapies. Here the authors use Cas9 to engineer lines that secrete PDGF-BB and VEFGA for improving wound healing.